2008
DOI: 10.1111/j.1472-765x.2008.02460.x
|View full text |Cite
|
Sign up to set email alerts
|

The detection of possible sensor histidine kinases regulating citrate/malate metabolism from the bovine rumen microbial ecosystem

Abstract: Aims:  To detect sensor histidine protein kinases (HPKs) similar to accessory gene regulator C (AgrC) from the rumen microbial ecosystem. Methods and the Results:  Genes related to sensor HPKs were amplified by PCR using two pairs of agrC‐specfic primers from DNA extracted from bovine rumen contents. The PCR products were cloned, sequenced and phylogenetically analysed. It appeared that two sequences were HPKs. Conclusions:  Although amino acid sequences deduced from the nucleotide sequences obtained in this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Feeding trials also confirmed that malic acid had a positive effect on increasing milk production in dairy cows (Sniffen et al, 2006;Devant et al, 2007;Wang et al, 2009b) and improving beef cattle performance (Martin et al, 1999;Castillo et al, 2007). Citric acid is another essential intermediate in the citric acid cycle, which has a similar function in stimulating rumen fermentation and improving animal performance (Packett and Butcher, 1963;Sun et al, 2008;Wang et al, 2009a).…”
Section: Introductionmentioning
confidence: 84%
“…Feeding trials also confirmed that malic acid had a positive effect on increasing milk production in dairy cows (Sniffen et al, 2006;Devant et al, 2007;Wang et al, 2009b) and improving beef cattle performance (Martin et al, 1999;Castillo et al, 2007). Citric acid is another essential intermediate in the citric acid cycle, which has a similar function in stimulating rumen fermentation and improving animal performance (Packett and Butcher, 1963;Sun et al, 2008;Wang et al, 2009a).…”
Section: Introductionmentioning
confidence: 84%
“…Increase of acetate production in the rumen would increase the amount of energy to the ruminant. Furthermore, citrate can stimulate rumen fermentation 13. It is suggested that small amounts of CA may have a catalytic effect on rumen microbial metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that small amounts of CA may have a catalytic effect on rumen microbial metabolism. Altering microbial metabolism offers a potential means of increasing feed efficiency 13. In fact, Packett and Butcher14 reported that the addition of sodium citrate at 2% to wether lamb diet resulted in a 47% increase in gain over the 86‐day feeding period and efficiency of utilization of feed was increased 23%.…”
Section: Introductionmentioning
confidence: 99%